Dietary patterns, beliefs and behaviours among individuals with inflammatory bowel disease: a cross‐sectional study. Issue 2 (14th June 2020) - Kamp, K. J.; Pennings, B.; Javelli, D.; Wyatt, G.; Given, B.
Abstract: Background: Inflammatory bowel disease (IBD) refers to a group of incurable gastrointestinal diseases that are common among young adults. The present study aimed to describe dietary intake, self‐modifications and beliefs among adults aged 18–35 years with IBD and to compare those with active versus inactive disease. National guidelines for daily intake include: 34 g of fibre for males and 28 g of fibre for females, 3 oz of whole grains, 1000 mg of calcium, <10% of added sugars, three cups of dairy, 2.5 cups of vegetables and two cups of fruit. Methods: Individuals with a diagnosis of IBD were recruited online using convenience sampling ( n  = 147). Data included a dietary screening questionnaire, self‐directed diet modifications, dietary beliefs questionnaire and demographics. Chi‐squared and t ‐tests were used to compare those with active versus inactive disease. Results: The sample was predominantly female (90%) and diagnosed with Crohn's disease (64%). Daily intake for females was 9.7 g of fibre, 0.3 oz of whole grains, 683.8 g of calcium, 1.1 of cups vegetables and 0.5 of cups fruit. Daily intake for males was 14.2 g of fibre, 0.4 oz of whole grains, 882.9 g of calcium, 1.4 cups of vegetables and 0.5 cups of fruit. Participants most often modified fibre (73%), fruits and vegetables (71%), grains (67%), and dairy (66%) as a result of their IBD. Eighty‐three percent believed that modifying their diet could reduce IBD symptoms. Conclusions: Both men and women with IBD struggle to meet the national guidelines for intake of fibre, whole grains, fruits and vegetables. The majority reported modifying their dietary intake as a result of IBD and expressed belief that diet could reduce symptoms. Abstract : The present study described dietary intake, self‐modifications and beliefs among adults aged 18–35 years with inflammatory bowel disease and compared those with active versus inactive disease. Individuals with inflammatory bowel disease commonly modified their diet, especially individuals who had active disease. The majority are modifying their diet without the guidance of a dietitian or nutritionist.